Buxoro amirligidagi ayrim etnik guruhlarning jamiyatning turli sohalarida tutgan o‗rni (SCIENCE and SOCIETY, 2023)
This article is mentioned that different national groups that lived in Bukhara Emirate participated in almost all spheres of social and economic life of the society and that they were legally allowed to live and trade here. National groups operating in khanates play an important role in all spheres of society. Among them, Bukhara Emirate stands out. We can clearly see that the representatives of